Quadro a quadro - Sá Júnior, Márcio Luiz de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
With the present poetic research I seek to investigate my creative process in what concerns the drawings of scenes from films in its smallest unit of time measurement, the frame translated into portuguese as "Quadro". In a research that prioritizes images, I emphasize the enjoyment of the non-verbal text that cinema allows us from art direction, for example, and frame by frame I talk about the film chosen for representation and add comments of a personal nature about the making of each artistic drawing using charcoal as primary material.

Busco com a presente pesquisa poética a investigação de meu processo criativo no que concerne o desenho de cenas de filmes em sua menor unidade de medida de tempo o frame traduzido para português como “quadro”. Em uma pesquisa que prioriza as imagens, enfatizo a fruição do texto não-verbal que o cinema nos permite a partir da direção de arte, por exemplo, e quadro a quadro discorro sobre o filme escolhido para representação e adiciono comentários de cunho pessoal sobre a feitura de cada desenho artístico empregando o carvão como material primordial.
Frame by frame
Keywords: Artistic drawing; Creative process; Desenho artístico; Cinema; Processo criativo